Modoc a new durum wheat for northern California - Y Puri; C Qualset; K Baghott; H Vogt; W Lehman; E Hempleman; W Shuey; J Prato (California Agriculture, 1976)
Modoc, a high-yielding, short-statured durum variety developed for the Tulelake area, produces grain of good for milling.